Natural Medicine Against the Sanitary State: Networks and Intersections Between the Anarchist and Naturist Movements in Chile (1920-1940); [la Medicina Natural Contra el Estado Sanitario: Redes E Intersecciones Entre Los Movimientos Anarquistas y Naturistas en Chile (1920-1940)] - Godoy-Sepulveda, E (Centro de Estudios Historicos de los Trabajadores y las Izquierdas, 2023)
This article investigates the scopes of naturist and anarchist discourses and practices, unraveling the points of encounter and disagreement between two projects of individual and collective transformation that put into practice a new way of understanding medicine and sanitary, promoting “healthy” and “rational” lifestyles. For this purpose, the historical development of naturism in Chile is studied in order to understand its philosophical bases and its perspectives on medical practices, to connect from this field its confluences with the anarchist movement, within which emerged expressions of the so-called “libertarian naturism”. © 2023, Centro de Estudios Historicos de los Trabajadores y las Izquierdas. All rights reserved.